Unveiling The Evolving Dynamics Of Mountain Pastoralism At Various Altitudinal Zones Of Upper Swat Valley, Pakistan - Nasir, Muhammad; Samiullah; Ur Rahman, Atta; Shah, Farooq; Ali, Zahid; Iqbal, Shahid (Migration Letters, 2024)
The confluence of environmental, climatic, and socioeconomic transformations is intensifying the vulnerability of pastoral social-ecological systems worldwide, with mountainous regions being excessively affected. This research paper explores the adaptive strategies employed by mountain pastoralists in Upper Swat, Pakistan, to navigate the complexities of rangeland management amidst dynamic climatic, social, and environmenta[1]l contexts. Through a comprehensive mixed-methods approach, involving observations, focus groups, and an extensive survey (2022-2023), this study reveals that mountain pastoralists have developed a multifaceted, adaptive strategy that integrates stall feeding with six distinct grazing mechanisms to optimize the use of spatially and seasonally heterogeneous rangeland resources. This strategy involves a coordinated sequence of winter stall-feeding near villages, spring rotational grazing in adjacent pastures, summer migration to high-elevation settlements, and intense autumn browsing of stubble fields prior to winter crop planting. The findings of this research contribute nuanced insights into the resilience and adaptability of mountain pastoralists and their rangeland management systems, informing the development of effective policies and programs to enhance the sustainability and reduce the vulnerability of mountain social-ecological systems.